Anime and Japanese: potential improvement of teaching meth- ods on the basis of preliminary survey (Journal of Oriental Studies, 2024)
Japanese anime and manga is considered as an integral part of Japa-nese popular culture. In recent years, it began to spread widely throughoutthe world. Especially, it has a significant impact on the youth identity inthe selection of foreign language and increasing the motivation of studentsto study Japanese language. Unfortunately, this issue has not been studiedin Kazakhstan yet. The article discusses the results of a preliminary surveyfor students to improve the methods of teaching Japanese language withJapanese anime and manga, and analyzed the views of the respondents.Key words: Japanese language, anime, questionnaire survey, teachingmethods, 日本語 nihongo, アニメ anime, アンケート anketa, 教授法kyoujuhou.